Evaluasi Pelaksanaan Pasca Pendidikan Keperawatan Berkelanjutan (PKB) Pada Perawatan Akhir Kehidupan Di Rumah Sakit X Jakarta - Fahruji, Azis; Yetti, Krisna; Mashudi, Dudi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Evaluation is an essential component of the continuing education process. Non-formal continuing nursingeducation program, consisting of seminars, training, workshops, conferences, symposiums, etc. End-of-lifepatient care is knowledge of the problems associated with illness and death, nursing competence is needed tomanage dynamic and complex situations around end-of-life care so that nurses who care for patients for daysfeel unready to provide care at the end of life. The aim is to evaluate the implementation of post-ContinuingNursing Education in the care of end-of-life patients by using fishbone. Case study design using frequencydistribution of test results, questionnaires and audit documentation with 75 samples then analyzed usingfishbone. The test results showed a value of> 85 (54.7%), understanding of the initial assessment showed avalue of> 85 (37.3%), the results of the documentation audit showed there was no documentation of 94% andthere was documentation of 6%. The nursing committee as a promoter of the implementation of activitiescoordinates with the field of nursing and nursing managers in carrying out evaluations of each continuingeducation program.